Patient Experience and Effective Communication and Patient Belief have Positive Prediction on Patient Loyalty to Use - Monica, Monica; Nofierni, Nofierni; Pamungkas, Rian (Alta Dharma Publisher, 2024)
Background: The decreasing number of patient visits is influenced by patient experiences that do not match their expectations. The patient's lack of trust and its medical staff still causes patients to not return for treatment. Objective: This study aims to analyse the association between patient experience and effective communication on patient loyalty through trust as an intervening variable. The sample for this study was outpatients who had been treated more than 2 (two) times at the internal medicine polyclinic at Dompet Dhuafa Integrated Health Home Hospital using BPJS insurance. The sample consisted of 280 people. The type of research is causality explanatory research with a cross-sectional approach. The sampling technique for this research uses a purposive sampling technique with statistical analysis using the Structural Equation Model (SEM) with Smart PLS software. The research results show that patient experience has a significant effect on BPJS patient loyalty through trust as an intervening variable seen from the R square value of 29.3% and effective communication has a significant effect on BPJS patient loyalty through trust as an intervening variable seen from the R square value of 33. 2%. It is recommended that hospital management be able to provide a good patient experience and effective communication by fostering a sense of trust from patients to increase loyalty to the hospital